PENGARUH BEBAN KERJA DAN DUKUNGAN SOSIAL TERHADAP STRES KERJA KARYAWAN - Ramadan Pasaribu; Fitri Khairani; Mairani Adelia; Najwa Aulia Putri; Suci Haryanti Manurung (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to explore in depth the role of industrial psychology in reducing job stress and enhancing employee well-being through a literature-based approach. Work-related stress is a significant challenge that affects both productivity and the mental and physical health of employees. Several factors, such as heavy workloads, lack of social support, and ineffective leadership, often act as triggers. This study finds that implementing principles of industrial psychology such as stress management training, improving workplace environments, and strengthening interpersonal relations can significantly mitigate job stress and increase well-being. The study underscores the importance of holistic and sustainable human resource management strategies as a foundation for establishing healthy and productive workplaces.